PENGARUH PERILAKU INOVATIF DAN KOHESIVITAS KELOMPOK KERJA TERHADAP KINERJA PEGAWAI - Liviansyah Liviansyah; Ratnawili Ratnawili (UM. Bengkulu, 2026)
This study aims to determine the innovative behavior and work group cohesiveness on employee performance in the Seluma regional government. This type of research is quantitative descriptive research. The population in this study were all Seluma regional government employees, with a sample of 64 respondents determined through proportionate stratified random sampling techniques. Data collection techniques were carried out through the distribution of questionnaires using a Likert scale. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis tests, and R2 determination coefficient tests, which were processed using the SPSS program. The results of this study indicate that innovative behavior has a positive and significant effect on employee performance. Workgroup cohesiveness also has a positive and significant effect on employee performance. Simultaneously, both have a positive and significant effect. This means that the better the innovative behavior and workgroup cohesiveness possessed by employees, the better the resulting performance. Thus, improved employee performance can be achieved by strengthening individual innovative behavior and building cohesive group collaboration within the organizational work environment. Kata Kunci : Innovative Behavior, Workgroup Cohesiveness, Employee Performance.